Eficiência do aparelho Herbst bandado na correção da Classe II divisão 1 -relato de caso - Landázuri, Denise Rocha Goes [UNESP]; Raveli, Dirceu Barnabé [UNESP]; Sampaio, Luana Paz; Santos-pinto, Ary Dos [UNESP]; Maia, Savana de Alencar [UNESP] (My University, 2013)
The current reports the case of a young patient with malocclusion Class II division 1 on permanent dentition treated in two stages, rthopedics and orthodontics, respectively. At first, the banded Herbst appliance was used duringa 7 months period, followed by a T4K appliance, Trainer for Kids used as retention, and on the second stage the corrective Orthodontics was performed. The results showed the acquirement of a Class I dental relationship, which was kept stable, with excellent intercuspation, even after 5 years of the removal of the Herbst appliance, as well as the correction of the overjet and the reduction of the facial profile convexity. It can be concluded that the Herbst appliance was very efficient in correcting the Class II malocclusion, long term, also providing a very favorable effect on the facial profile.

O presente artigo discorre sobre o caso de uma paciente com má oclusão Classe II, divisão 1, na fase da dentadura permanente jovem, que foi tratada em duas fases, ortopédica e ortodôntica, espectivamente. Na primeira, foi utilizado o aparelho Herbst bandado por um período de 7 meses, seguido do aparelho T4K, Trainer for Kids, utilizado como contenção e, na segunda fase, foi realizada a Ortodontia corretiva. Os resultados mostraram a obtenção de uma relação dentária de Classe I, que permaneceu estável, mesmo 5 anos após a remoção do aparelho de Herbst, assim como a correção da sobressaliência e a redução da convexidade do perfil facial. Pode-se concluir que o aparelho de Herbst foi bastante eficiente na correção da Classe II, a longo prazo, proporcionando também um efeito muito favorável sobre o perfil facial.
Efficiency of the banded Herbst appliance in Class II division 1 correction: case Report
Keywords: Malocclusion; Angle Class II; Herbst appliance; Cephalometry; Má oclusão de Angle Classe II; Aparelho de Herbst; Cefalometria